A teenage boy with Systemic Lupus Erythematosus complicated with acquired von willebrand syndrome: a rare case and challenging in making diagnosis - Sabtu, Noor Hayati; Idris, Faridah; Tohit, Eusni Rahayu; Abu Bakar, Azlinda; Wan Yusof, Wan Aswani; Osman, Raudhawati (Fakulti Perubatan Dan Sains Kesihatan, UPM, 2023)
In systemic lupus erythematosus (SLE), haematological abnormalities are frequent, although they are an uncommon cause of acquired von Willebrand syndrome (AVWS). AVWS is a rare condition that can cause a bleeding disorder. We presented a case of AVWS in the early diagnosis of SLE. One month before admission, the patient had a history of recurrent epistaxis. He presented to the hospital with symptomatic anaemia and was noted to have severe anaemia with iron deficiency. During hospitalisation, recurrent epistaxis recurred and was found to have prolonged activated partial thromboplastin time (aPTT), presence of lupus anticoagulant (LA), and lower von Willebrand factor (VWF), and factor 8 (VIII) levels. Simultaneously, he was diagnosed with SLE based on Systemic Lupus International Collaborating Clinics (SLICC) criteria. He underwent blood transfusions and was treated with immunosuppressive drugs such as steroids, mycophenolate mofetil, and an anti-fibrinolytic agent; he subsequently stopped bleeding and showed clinical improvement.